2022
DOI: 10.1515/mt-2021-2138
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid engineering algorithm of the seeker algorithm and particle swarm optimization

Abstract: A newly hybrid algorithm is proposed based on the combination of seeker optimization algorithm and particle swarm optimization. The hybrid algorithm is based on a double population evolution strategy, and the populations of individuals are evolved from the seeker optimization algorithm and the particle swarm optimization separately. The populations of individuals employ an information sharing mechanism to implement coevolution. The hybrid algorithm enhances the individuals’ diversity and averts fall into the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The algorithm combined with PSO algorithm and used the information sharing mechanism to achieve co-evolution, which increased the diversity of individuals. The study's suggested method was shown to have the best resilience and optimization seeking abilities when compared to other algorithms, according to evaluation results [9]. Abadi MQ H and other scholars proposed the HSSAGA model to address the scheduling problem of medical personnel during the COVID-19 epidemic.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm combined with PSO algorithm and used the information sharing mechanism to achieve co-evolution, which increased the diversity of individuals. The study's suggested method was shown to have the best resilience and optimization seeking abilities when compared to other algorithms, according to evaluation results [9]. Abadi MQ H and other scholars proposed the HSSAGA model to address the scheduling problem of medical personnel during the COVID-19 epidemic.…”
Section: Related Workmentioning
confidence: 99%
“…When the firefly technique is used, it can result in "storage" and assist particles in leaving the local optimal solution and reexamining it. Equation represents the local search position update when the "elite solution" is the cause of the current solution (9).…”
Section: Optimization and Improvement Of Cs Strategiesmentioning
confidence: 99%